Strengthening social capital in the Sri Lankan population: A qualitative exploration of factors driving the mothers' support groups initiative during economic crisis - Millawage Supun Dilara Wijesinghe; Upeksha Gayani Karawita; Nissanka Achchi Kankanamalage Ayoma Iroshanee Nissanka; Balangoda Muhamdiramlage Indika Gunawardana; Weerasinghe Mudiyanselage Prasad Chathuranga Weerasinghe; Vithanage Chandima Nayani Vithana; Kanchana Lanka Kumari Mahagamage; Singappuli Arachchilage Sanjeewanie Champika Karunaratne; Ranjith Batuwanthudawe (Tabriz University of Medical Sciences, 2023)
Background: Social capital is a concept that has been identified to improve health outcomes in many populations. Due to COVID-19 and many other factors, Sri Lanka faced a massive economic crisis that affected the nutrition of communities. Many community engagement initiatives have begun to promote the country's nutrition during the worst-hit years. The Mothers' Support Groups initiative is one of the existing community engagement initiatives that is well known for strengthening community social capital. This article discusses how the Mothers' Support Groups (MSG) initiative in Sri Lanka contributed to improving social capital in Sri Lanka during the economic crisis, focusing on nutrition. Methods: We conducted a case study on the activities undertaken by mothers' support groups in view of how they focused on social capital. We selected all activities presented by districts that improved social capital related to nutrition promotion captured in the YouTube video stream. We analyzed these qualitative data to identify the main themes related to social capital and nutritional promotion. Two coders transcribed the video recordings. We analyzed the data using the iterative thematic inquiry (ITI) method and initially assessed beliefs about concepts, building new beliefs through encounters with data, listing tentative themes, and evaluating themes through coding. Results: Six major themes were identified (that social capital had been strengthened to promote nutrition): awareness creation of nutrition, home gardening promotion, promoting livestock farming, minimizing food waste, improving the home economy, and psychosocial health promotion. The most common forms of social capital encountered in these themes were bonding, bridging, and linking. Furthermore, strengthening structural social capital is more prominent than strengthening cognitive social capital. Conclusion: Social capital can improve nutritional status during crises. Activities that can be used to achieve this vary from simple awareness creation among communities to more advanced psychosocial health promotion. Overall, social capital contributed to the community development aspect of health promotion to a greater extent.